Entrepreneurial skill acquisition and youth's self-employment in Malaysia: how far? - Isidore Ekpe; Razli Che Razak; Mohammad Ismail; Zulhamri Abdullah (Mediterranean Center of Social and Educational Research Publishing, 2015)
The objective of this study was to examine the moderating effect of self-motivation on the relationship between entrepreneurial skill acquisition and self-employment practice among graduates from Malaysian public universities. It is a known fact that youth enterprises could generate employment opportunites and lead to economic growth of a country; however, researches have reported that most of entrepreneurship graduates from Malaysian universities do not go into entrepreneurship practice five years after graduation. To test this relationship, a conceptual model was developed based on Ajzen (1991) theory. The study recommended that Malaysian government and community leaders should draft appropriate strategies (for example counseling in school), that will encourage and engender greater participation of the youths in self employment practice.